The Cultural Context of Economic Changes - Cierniak-Szóstak, Ewa (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The economics sciences more and more often connects cultural variables to economic change processes. The article considers several theoretical and methodological issues in the analysis of culture, and in the way economic culture is used in studies on processes of economic change on various levels: at the macro-level of national economic culture in the search for historically rooted cultural values conducive to economic development; at the mezo-level of the economic culture of various social groups, communities and cities; and at the micro-level of organisational culture, which is a significant component of economic culture.